What encourages people to carpool? A conceptual framework of carpooling psychological factors and research propositions. (December 2021) - Julagasigorn, Puthipong; Banomyong, Ruth; Grant, David B.; Varadejsatitwong, Paitoon
Highlights: Identifies psychological theories applicable for carpooling research. Identifies psychological factors motivating carpooling for drivers and passengers. Proposes a conceptual framework for future carpooling research. Specifies six research propositions for such future research. Suggests eight additional research directions to complement such research. Abstract: Carpooling brings benefits to carpool participants and the environment and society. Literature has called for a better understanding of psychological factors encouraging people to carpool however current research does not provide an in-depth psychological understanding of carpooling behaviour. This paper provides a review of psychological factors motivating drivers and passengers to carpool and identifies psychological theories appropriate for carpooling research. The Theory of Planned Behaviour and Norm-Activation Model were used as a priori theoretical frameworks to undertake a systematic literature review to identify important factors and relevant theories. Eighteen psychological factors were identified and classified as either common for drivers and passengers or specific to each group. In addition to the a priori frameworks, Consumer Perceived Value, Social Capital, and Technology Acceptance Model are considered the most appropriate for carpooling research. A conceptual framework and six research propositions were developed. Further, eight additional directions for future research were suggested including employing a variety of data collection methods to ensure rigour; collecting more data from non-Western countries for contextual veracity; exploring and testing psychological factors more deeply; and investigating the impact of COVID-19 on carpooling decisions. This paper contributes to theory through the development of the conceptual framework, identifying research propositions and providing additional research directions. The identified factors can be considered by researchers, matching agencies, and policy-makers to better promote carpooling.